Diagnóstico del pavimento rígido de la vía del barrio Diamante etapa I del municipio de Cartago, Valle del Cauca (2021)
Regarding the general objective proposed for this work, to diagnose the types of damage caused in the rigid pavement presented in the main road of the Diamante neighborhood stage I located in the Cartago Valle municipality, it can be concluded that the diagnosis of the road pavement failures located in the Diamante neighborhood stage I, Cartago Valle del Cauca municipality.